2013
DOI: 10.3390/ijgi2030553
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Source Data Processing Middleware for Land Monitoring within a Web-Based Spatial Data Infrastructure for Siberia

Abstract: Land monitoring is a key issue in Earth system sciences to study environmental changes. To generate knowledge about change, e.g., to decrease uncertaincy in the results and build confidence in land change monitoring, multiple information sources are needed. Earth observation (EO) satellites and in situ measurements are available for operational monitoring of the land surface. As the availability of well-prepared geospatial time-series data for environmental research is limited, user-dependent processing steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…There are also several other web-based systems that provide tools to search, order, and download RS data; these include the USGS Earth Explorer [228] for data analysis, the National Climatic Data Center-NCDC Climate WebGIS (http://www.climate.gov/#dataServices), the NASA Giovanni [229] or the Eearth Observation Data Service (http://www.earthserver.eu/services/eods) for the RS community, the PlanetServer for the Planetary science community [230], and single web services and free software solutions for automatically generated 3D point clouds for UAVs [231]. Eberle et al [232] demonstrated how different web services can be embedded to generate a geo-data toolbox for monitoring forest in Siberia using RS data. Other novel developments of geospatial web services are oriented toward a server-based on-demand access and processing of big Earth data [230].…”
Section: Handling Petabyte-scale Rs Data With Cloud and Web Servicesmentioning
confidence: 99%
“…There are also several other web-based systems that provide tools to search, order, and download RS data; these include the USGS Earth Explorer [228] for data analysis, the National Climatic Data Center-NCDC Climate WebGIS (http://www.climate.gov/#dataServices), the NASA Giovanni [229] or the Eearth Observation Data Service (http://www.earthserver.eu/services/eods) for the RS community, the PlanetServer for the Planetary science community [230], and single web services and free software solutions for automatically generated 3D point clouds for UAVs [231]. Eberle et al [232] demonstrated how different web services can be embedded to generate a geo-data toolbox for monitoring forest in Siberia using RS data. Other novel developments of geospatial web services are oriented toward a server-based on-demand access and processing of big Earth data [230].…”
Section: Handling Petabyte-scale Rs Data With Cloud and Web Servicesmentioning
confidence: 99%
“…The trend analysis results from the previous section have shown the transition seasons to be characterized by positive temperature trends with a decline in maximum snow water equivalent for the area of the Taymyr peninsula. Daily air temperature (T air ) information from meteorological stations in this region are showing an increase during the last 40 years by approximately 3 °C (Figures 6 and S2), with an intensification of peak temperature events during the summer months [88,89].…”
Section: High-resolution Change Mapping Of the Taiga-tundra Transitiomentioning
confidence: 99%
“…Implementation of the analysis in Geoportal needs some middleware software preparation (Fig.2). Similar approach concerning middleware can be found (Eberle et al 2013). Vector data gathered in Geoportal are converted to raster model (V/R conversion), reclassified into 0/1 map, distance from the feature is calculated, next standardization and weighting is needed, finally the criterions are merged.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning satellite image processing following projects can be mentioned: forest monitoring -(EU-FP7 ZAPÁS PROJECT), cloud-based implementations, algorithms performing an atmospheric correction, land use classification and extraction of Leaf Area Index (LAI) for vegetated areas, Siberian forest monitoring (Eberle et al 2013(Eberle et al , 2014, project APPS4GMES -operational system for Landsat data for all Germany, MELODIES Project -"technical platform", which applies cloud computing etc. The mentioned platforms are relatively new so it is not now possible to give any statistics about the long-live application.…”
Section: Geoportal Kielcementioning
confidence: 99%